Measuring Ethical Sensitivity and Evaluation - Shawver, Tara J. (Journal of business ethics, 2009)
Measures of student ethical sensitivity and their increases help to answer questions such as whether accounting ethics should be taught at all. We investigate different sensitivity measures and alternatives to the well-established Defining Issues Test (DIT-2, Rest, J. R. et al. [1999, Postconventional Moral Thinking: A Neo-Kohlbergian Approach (Lawrence Erlbaum Associates, Mahwah, NJ]), frequently used to measure the effects of undergraduate accounting ethics education. Because the DIT measures cognitive development, which increases with age, the DIT scores for younger accounting students are typically lower, have limited range, and are not likely to vary sufficiently with corresponding choices in ethical dilemmas. Since the DIT measures only the moral judgment component of ethical decision-making, we consider the multidimensional ethical scale (MES) to allow respondents to provide explanations for their moral and other judgments. The MES has been used to measure attitudes related to justice, utility, contractualism, egoism, and relativism. Unfortunately, the MES is not comparable in one-dimension to the DIT, and unlike the DIT, the MES has no theoretical or objective base. Therefore, we construct a comparable one-dimensional relative measure, a Composite MES Score, obtained from previous research on practicing accountants. We compare the reliability of this measure to the DIT in explaining the ethical choices of 54 specially chosen, somewhat homogeneous students, whose ages range from 18 to 19, and who are taking a second semester freshman accounting course at a private, religion-affiliated university. These particular students are relatively untrained in the formal use of questionable accounting choices. These students are less likely to recognize the dilemmas of the MES and are also less likely to demonstrate sufficient variation in their DIT scores, traditionally low for freshmen students. As freshmen, they are recent graduates of high school and more likely guided by other ethical influences including friends, family, or contractual obligations (some of the MES constructs) rather than higher cognitive development. This study confirms suspicions. We find the DIT scores do not vary sufficiently to explain the moral reasoning of freshmen. For eight dilemmas and 24 choices we find the DIT score correlates with only three choices, whereas the MES regression models have at least one significant construct for 23 out of 24 ethical choices. The Composite MES Score (a relative measure) also explains 23 out of 24 choices and is statistically related to the DIT in only one of the choices. Unlike the DIT, the Composite MES permits pretest and retesting with different dilemmas to evaluate changes in ethical sensitivity. These results argue for relative rather than absolute measures of sensitivity and guides beyond cognitive development (the DIT-score) to explain undergraduate student sensitivity.